Vaping Among Malaysian Students 2022–2024: A Systematic Review of Prevalence, Awareness and Influencing Factors - Ronald Eden, Vitalis; Hamid, Hazrina; Mohamad, Mohd Sabri; Kanti Das, Sreemoy; Iii Dioso, Regidor (Malaysian Journal of Medical Sciences, 2025)
The increasing prevalence of e-cigarette use among students in Malaysia has raised significant public health concerns. Although various individual studies have explored this issue across different educational settings, a consolidated understanding of usage patterns, awareness, and influencing factors remains limited. This systematic review aims to synthesise the current evidence on the prevalence, knowledge, attitudes, and determinants of e-cigarette use among students in Malaysian higher education institutions. We conducted a systematic search across major databases, including PubMed, Scopus, and Google Scholar, to identify relevant cross-sectional studies published between January 2022 and December 2024. The inclusion criteria focused on peer-reviewed articles involving students from universities and colleges in Malaysia aged 17 to 40 years. Data extraction captured prevalence rates, participant demographics, knowledge and attitudes toward vaping, and key influencing factors. Nine studies, encompassing data from 2,828 students across diverse geographic and academic settings in Malaysia, met the inclusion criteria. The reported prevalence of e-cigarette use ranged from 2.9% to 32%, with considerable variation across regions and academic disciplines. Peer influence emerged as the most frequently cited determinant of use, followed by social trends, media exposure, and stress relief. While general awareness of e-cigarettes and their risks was relatively high, gaps in knowledge and preventive behaviours were consistently observed. Institutions with a healthcare-focused curriculum demonstrated lower prevalence rates and higher knowledge scores. Although awareness of e-cigarette risks is widespread among students, inconsistent knowledge and insufficient behavioural interventions persist, highlighting the need for targeted health education initiatives and peer-led prevention strategies.